Strong, weak David Cameron. (Economist, 2011)
The article focuses on British prime minister David Cameron's handling of Britain's deployment in Afghanistan and ongoing revelations of phone-hacking by the tabloid "News of the World." It states that while only around 40 percent of British voters believe Britain's presence in Afghanistan helps protect national security, there is dislike over the thought of losing a war. It mentions that he bowed to calls by the Labour Party for a public inquiry about phone-hacking after a criminal probe.